"NO M'ESTIMIS MASSA; ESTIMA'M SÀVIAMENT": LA CONSTRUCCIÓ LITERÀRIA DE LA IDENTITAT MONSTRUOSA DE BARCELONA. (1st June 2021) - CASACUBERTA, MARGARIDA
Abstract : This article aims to analyze the process of literary construction of the "monstrous" identity of Barcelona. Specifically, it examines and contextualizes the literary images of the city-as-woman from the mid-nineteenth century until Francoism. The metaphor of Barcelona as a woman is articulated around two axes: the idealization of the city as a compliant and submissive woman, and its monsterification as a rebel woman. Both processes are inextricable and serve to justify (symbolically and literally) the political control of the city.